Research in Practice: Preservice Teachers of the Deaf Action Research With DHH K–12 Learners and Self-Graphing. - Beal, Jennifer S. (American Annals of the Deaf)
When an instructional strategy lacks evidence of its effectiveness with certain learner groups, educators can conduct action research in their classroom to determine strategy effectiveness. In the present study, seven preservice teachers of the deaf (TODs) implemented self-graphing interventions with deaf/hard of hearing (DHH) learners to change target on- and off-task behaviors. Preservice teachers were master's-level candidates in a university teacher preparation program. DHH learners were 5–16 years old, attended general education classrooms at their local schools or schools for the deaf, and used multiple forms of communication/language. Candidates successfully completed ABAB design studies, and three candidates collected maintenance data after the interventions were withdrawn. They conducted their studies with high interobserver agreement. All DHH learners changed their target behavior when self-graphing was introduced. This study expands self-graphing evidence from high-incidence disability groups to a diverse group of DHH students.